Combination of ablative fractional carbon dioxide laser and platelet-rich plasma treatment to improve hypertrophic scars: a retrospective clinical observational study. Issue 1 (28th July 2021) - Dai, Zhanzhan; Lou, Xiaozhen; Shen, Tuo; Sun, Yu; Xiao, Yongqiang; Zheng, Xingfeng; Wang, Xuexin; Peng, Yu; Guo, Yukun; Guo, Yibin; Wen, Jiannan; Fang, He; et al.
Abstract: Background: Hypertrophic scars are one of the main complications that affect the quality of life of patients after burns. Many methods have been shown to be effective in the treatment of hypertrophic scars, such as ablative fractional CO2 laser (AFCL) and platelet-rich plasma (PRP). However, there are few studies on the effect of the combined application of these measures. The purpose of this study was to explore the therapeutic effect of AFCL combined with PRP on hypertrophic burn scars. Methods: A retrospective clinical observation study was conducted on 50 patients with hypertrophic burn scars. The AFCL+PRP group included 31 patients who received AFCL combined with PRP treatment; the AFCL group included 19 patients who received AFCL treatment only. The University of North Carolina 4P Scar Scale (UNC4P) and the Vancouver Scar Scale (VSS) scores that were collected before each treatment were used as indicators of the effectiveness of the previous treatment. The scores recorded at the second, fourth and seventh months were analysed. Results: The demographic data of the 2 groups were not significantly different. Before treatment, there was no difference in the UNC4P and VSS scores between the 2 groups. There was a significant decline in the UNC4P and VSS total scores over 6 months in both groups ( p  < 0.05) and scores in the 2 groups were comparable after 3 and 6 months ( p  < 0.05). UNC4P scores in the AFCL+PRP group decreased from a mean of 8.26 to 2.61 ( p  < 0.05) with a concomitant drop in VSS scores from a mean of 11.74 to 6.06 ( p  < 0.01). In the AFCL group UNC4P and VSS scores decreased from 7.68 to 4.63 ( p  < 0.05) and from 10.89 to 8.16 ( p  < 0.05), respectively. The sub-items of these 2 assessments were analysed and the results suggest that AFCL combined with PRP can comprehensively improve scarring. Conclusions: This study shows that PRP is an effective adjunct for AFCL in the treatment of hypertrophic burn scars and that the combination of PRP and AFCL proved to be more useful than AFCL alone. This combination may be a new and effective clinical practice for the treatment of scars. However, larger and higher-level clinical studies are still needed to determine its efficacy and possible mechanisms.